Strengthening civic literacy through learning civic education courses at Ahmad Dahlan University - Sukmayadi, Trisna; Abdulkarim, Aim; Komalasari, Kokom; Siti Masyitoh, Iim (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This research is driven by the significance of civic education in cultivating students' knowledge and comprehension of citizenship, democracy, human rights, and social responsibility. This course at Ahmad Dahlan University is integral to an institutional initiative aimed at enhancing students' civic literacy. Nonetheless, initiatives to enhance civic literacy via the examination of these courses require more assessment. This research aims to examine the civic education course's role in enhancing students' civic literacy. Data was gathered by observation, interviews, and literature review. Analysis involves the collection of facts, presentation, and formulation of findings. The findings indicated that the project-based learning paradigm employed in the civic education course at UAD was beneficial in enhancing students' civic literacy, particularly in relation to democracy and national identity. Interactive pedagogical approaches, such as case studies, enhance students' comprehension of social concerns. Social contextual elements, pedagogical models and methodologies, together with assessment, significantly impact students' motivation and academic performance. Project-based learning surpasses traditional techniques in effectiveness, while regular assessments provide the adaptation of learning models and strategies to meet student requirements, thereby enhancing engagement and motivation.